2020
DOI: 10.1002/rmv.2184
|View full text |Cite
|
Sign up to set email alerts
|

Airborne transmission of SARS‐CoV‐2 via aerosols

Abstract: A key consideration in the Covid-19 pandemic is the dominant modes of transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. The objective of this review was to synthesise the evidence for the potential airborne transmission of SARS-CoV-2 via aerosols. Systematic literature searches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 45 publications
1
65
0
3
Order By: Relevance
“…The countries with the most infections include the USA, India, Brazil, Mexico, Spain, Russia, Germany, France, Italy, the United Kingdom and China ( Gozali, 2020 ; WHO, 2020 ). Despite meteorological factors, air pollution might be one of the environmental drivers that exacerbated the risk of death due to COVID-19 as it may be possible for the virus to be transmitted via aerosols, adsorbed onto particulate matter or be airborne ( Comber et al, 2020 ; Prather et al, 2020 ; van Doremalen et al, 2020 ). Sanità di Toppi et al (2020) reported that COVID-19 virus was detected in aerosols up to three hours after aerosolization.…”
Section: Introductionmentioning
confidence: 99%
“…The countries with the most infections include the USA, India, Brazil, Mexico, Spain, Russia, Germany, France, Italy, the United Kingdom and China ( Gozali, 2020 ; WHO, 2020 ). Despite meteorological factors, air pollution might be one of the environmental drivers that exacerbated the risk of death due to COVID-19 as it may be possible for the virus to be transmitted via aerosols, adsorbed onto particulate matter or be airborne ( Comber et al, 2020 ; Prather et al, 2020 ; van Doremalen et al, 2020 ). Sanità di Toppi et al (2020) reported that COVID-19 virus was detected in aerosols up to three hours after aerosolization.…”
Section: Introductionmentioning
confidence: 99%
“…The role of SARS-CoV-2 airborne spreading in the current pandemic is still under debate, although there is growing evidence that susceptible individuals might be infected by this route of transmission [7][8][9] Although this method needs further optimization, it can be readily used for SARS-CoV-2 airborne surveillance. The procedure is easy to handle, cost efficient and suitable to be used worldwide even in emerging and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence for a transmission of SARS-CoV-2 via aerosols. [7][8][9] However, only a few studies have been published to date. Liu et al reported SARS-CoV-2 RNA concentrations in different areas of two hospitals in Wuhan.…”
Section: Introductionmentioning
confidence: 99%
“…Recovered COVID-19 positive residents stayed in the COVID-19 positive area despite limited evidence for immunity, as no human reinfection had yet been confirmed [ 23 ]. Droplets, direct contact and possibly aerosols were assumed to be the primary mode of transmission of SARS-CoV-2 [ 4 ]. As testing capacity was still limited, no environmental samples were tested for SARS-CoV-2 in the facility.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 is transmitted by both respiratory droplets (> 5 µm) and contact with respiratory secretions. The contribution of aerosols (particles ≤ 5 µm which can be spread over larger distances) is not yet clear [ 4 ].…”
Section: Introductionmentioning
confidence: 99%